Successful chemotherapeutic treatment for metastatic littoral cell angioma: A case report. Issue 15 (April 2018) - Takayoshi, Kotoe; Doi, Goro; Tsuruta, Nobuhiro; Yoshihiro, Tomoyasu; Nio, Kenta; Tsuchihashi, Kenji; Ariyama, Hiroshi; Odawara, Jun; Shimoda, Shinji; Kohashi, Kenichi; Oda, Yoshinao; Itoh, Shinji; et al.
Abstract: Rationale: Metastatic littoral cell angioma (LCA) is extremely rare. No standard therapeutic strategy has been established, and the impact of chemotherapy has not yet been evaluated. Patient concerns: A 61-year-old woman was admitted because of bicytopenia. She had a splenectomy for LCA of the spleen 10 years earlier. Bone marrow aspiration was normal, and a computed tomography (CT) scan showed hepatomegaly with multiple liver tumors. Diagnoses: Liver biopsy samples showed macrophage-like cell infiltration in the hepatic sinusoids. Metastatic LCA was diagnosed based on immunohistochemistry, imaging tests, and the clinical course. Interventions: Immunosuppressive agents, such as prednisolone and cyclosporine, were ineffective. Next, cytotoxic agents, such as etoposide, paclitaxel, and vincristine, were administered. Outcomes: Cytotoxic agents showed a prominent effect against LCA. CT showed improvement of the hepatomegaly, and fluoro-deoxyglucose (FDG) uptake decreased markedly at a follow-up FDG- positron emission tomography (PET) scan. Lessons: Chemotherapeutic treatment based on hemophagocytic syndrome or angiosarcoma might have anti-tumor activity against metastatic LCA. Analysis of the molecular characteristics of this tumor is needed to develop better treatment options.